2017
DOI: 10.1002/jssc.201601201
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of 12 active components in the roots ofPulsatilla chinensisusing tissue-smashing extraction with liquid chromatography and mass spectrometry

Abstract: Ultra high performance liquid chromatography coupled with mass spectrometry and combining a tissue-smashing extraction technique was developed for the simultaneous quantitative analysis of 12 compounds in the roots of Pulsatilla chinensis. Among them, compound 6 was characterized and accurately quantified in this herb for the first time. The parameters of extraction condition were simultaneously optimized with a Box-Behnken design and Derringer's function. The optimized conditions were as follows: sample quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Compared with the HPLC and HPTLC methods, the UHPLC-ESI-MS/MS method in multiple reaction monitoring (MRM) acquisition mode is more effective in rapidly quantifying trace compounds due to its rapid separation power, low detection limit, better accuracy, high specificity, and resolution [12,[35][36][37][38][39].…”
mentioning
confidence: 99%
“…Compared with the HPLC and HPTLC methods, the UHPLC-ESI-MS/MS method in multiple reaction monitoring (MRM) acquisition mode is more effective in rapidly quantifying trace compounds due to its rapid separation power, low detection limit, better accuracy, high specificity, and resolution [12,[35][36][37][38][39].…”
mentioning
confidence: 99%
“…Modern studies have shown that it has anti‐inflammatory, antibacterial, antioxidant, antitumor, and other pharmacological effects [1–15], leading to its application in proprietary Chinese medicine. Triterpenoid saponins were predominant biologically active constituents, and these were subcategorized into lupane and oleanane saponins on skeletal basis [16, 17]. Nonetheless, various look‐alike species are marketed and sold as P. chinensis (Bge.)…”
Section: Introductionmentioning
confidence: 99%
“…Modern studies have shown that it has anti-inflammatory, Article Related Abbreviations: EMRT, exact mass retention time; OPLS-DA, orthogonal partial least square discriminant analysis; PCA, principal component analysis; RT, retention time antibacterial, antioxidant, antitumor, and other pharmacological effects [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15], leading to its application in proprietary Chinese medicine. Triterpenoid saponins were predominant biologically active constituents, and these were subcategorized into lupane and oleanane saponins on skeletal basis [16,17]. Nonetheless, various look-alike species are marketed and sold as P. chinensis (Bge.)…”
Section: Introductionmentioning
confidence: 99%
“…Hederacoside C (3‐[{2‐ O ‐(α‐ l ‐rhamnopyranosyl)‐α‐ l ‐arabinopyranosyl}oxy]‐23‐hydroxyolean‐12‐en‐28‐oicacid6‐ O ‐{4‐ O ‐(α‐ l ‐rhamnopyranosyl)‐β‐ d ‐glucopyranosyl}‐β‐ d ‐glucopyranosyl ester, HDC) is a chief bioactive natural triterpenoid saponin . It is not only widely found in the Pulsatilla Adans , but also existed in the Hedera helix .…”
Section: Introductionmentioning
confidence: 99%